Flight from the Reich refugee Jews, 1933-1946 - Dwork, Deborah; Pelt, R. J. van (New York : W.W. Norton, 2009)
Discusses the legal and illegal ways that millions of Jews managed to leave Germany, the challenges they faced, and the diversity of the refugee experience.
Includes bibliographical references (p. [381]-447) and index.